Дослідження коливальних спектрів фулерену С80 і його окису С80−О на основі U(2) алгебри Лі - Sen, R.; Kalyan, A.; Paul, R.S.; Das, R.; Choudhury, J.; Sarkar, N.K.; Bhattacharjee, R. (Publishing house "Academperiodika", 2012)
Using the Lie algebraic method, the stretching vibrational energies of fullerene C80 & its epoxide C80–O are calculated in the one-dimensional U(2) framework. By constructing the model Hamiltonian with the help of Casimir and Majorana invariant operators in this framework, we calculated the local mode vibrational energy levels of fullerene C80 & C80–O.